2021
DOI: 10.5194/amt-14-5139-2021
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mobile monitoring data from the microAeth® MA200 for measuring changes in black carbon on the roadside in Augsburg

Abstract: Abstract. The portable microAeth® MA200 (MA200) is widely applied for measuring black carbon in human exposure profiling and mobile air quality monitoring. Due to it being relatively new on the market, the field lacks a refined assessment of the instrument's performance under various settings and data post-processing approaches. This study assessed the mobile real-time performance of the MA200 to determine a suitable noise reduction algorithm in an urban area, Augsburg, Germany. Noise reduction and negative va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…For example, particulate matters (PMs), which refer to tiny particles in the air adsorbing polycyclic aromatic hydrocarbons (PAHs), heavy metals, and other volatile organic fragments, can be breathed into human lungs leading to pulmonary diseases ( Araujo, 2011 ) and enter blood circulation to induce cardiovascular diseases ( Lawal, 2017 ). Black carbon (BC) belongs to PMs and is generated from incomplete combustion ( Liu et al, 2021a ), which showed potential carcinogenic effects on human ( Arif and Parveen, 2021 ). O 3 is a very reactive and oxidative pollutant, which can damage the human skin, eyes, and mucosae ( World Health Organization, 2003 ) as well as cause inflammation in bronchia leading to respiratory diseases ( Kim et al, 2020 ; Szyszkowicz and Rowe, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, particulate matters (PMs), which refer to tiny particles in the air adsorbing polycyclic aromatic hydrocarbons (PAHs), heavy metals, and other volatile organic fragments, can be breathed into human lungs leading to pulmonary diseases ( Araujo, 2011 ) and enter blood circulation to induce cardiovascular diseases ( Lawal, 2017 ). Black carbon (BC) belongs to PMs and is generated from incomplete combustion ( Liu et al, 2021a ), which showed potential carcinogenic effects on human ( Arif and Parveen, 2021 ). O 3 is a very reactive and oxidative pollutant, which can damage the human skin, eyes, and mucosae ( World Health Organization, 2003 ) as well as cause inflammation in bronchia leading to respiratory diseases ( Kim et al, 2020 ; Szyszkowicz and Rowe, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we calculated hourly concentration of eBC by time integrating the instrument's data collection frequency of 5-minute and found that the hourly averaged eBC concentrations from individual MA300 units were well correlated with the reference measurements. In future applications of the MA300, trade-offs between high temporal resolution and increased noise should be considered (Liu et al, 2021;Hagler et al, 2011), recognizing that temporal integration can alleviate the unit specific measurement noise. From the MA300's raw photometer readings, we identified presence of instrumental drift across the units.…”
Section: Discussionmentioning
confidence: 99%
“…Portable but effective instruments are often required for mobile monitoring, in-vehicle commuter exposure (Weichenthal et al, 2015;Apte et al, 2011), indoor personal exposure (Jeong and Park, 2017), and for monitoring wildfire smoke using unmanned aerial vehicles. (Aurell et al, 2021) Over the past decade, researchers have become increasingly interested in micro-aethalometers, as they are suitable for characterizing emissions in these challenging micro-environments (Alas et al, 2020;Aurell et al, 2021;Liu et al, 2021). The newly developed micro-aethalometer model MA300 (AethLabs) uses similar measurement techniques to the AE33 but with a smaller form factor, a built-in rechargeable battery, and a low-volume pump, making it suitable for indoor measurements and personal exposure analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Pirjola et al 2016, Wren et al 2018, Järvinen et al 2019, Chambliss et al 2020, Lepistö et al 2022 and next-to-source experiments (e.g. Dallmann et al 2013, Liu et al 2021, Saarikoski et al 2021. Results of many field studies do not represent a single BC source, but e.g.…”
Section: Introductionmentioning
confidence: 99%